2020
DOI: 10.30802/aalas-jaalas-19-000061
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Mouse Health Monitoring Between Soiled-bedding Sentinel and Exhaust Air Dust Surveillance Programs

Abstract: To monitor rodent colony health in research facilities, soiled-bedding sentinel (SBS) animals have traditionally been used. SBS can be tested by various methods, which may include serology, PCR analysis, and necropsy. Several pathogens are unreliably detected by using SBS or transmitted poorly through soiled bedding, and collection and evaluation of SBS samples can be time-intensive. Recently, exhaust air dust (EAD) testing through PCR analysis has emerged as an adjunct or replacement method for rodent colony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Until now, EAD-based monitoring approaches proved to be suitable for a broad variety of infectious agents, such as MNV [ 161 , 167 ], MHV [ 158 ], Murine Astrovirus [ 168 ], Lactate–Dehydrogenase–Elevating–Virus (LDEV) [ 169 ], Rodentibacter sp. [ 153 , 162 ], Helicobacter sp.…”
Section: How To Ensure Qualitymentioning
confidence: 99%
“…Until now, EAD-based monitoring approaches proved to be suitable for a broad variety of infectious agents, such as MNV [ 161 , 167 ], MHV [ 158 ], Murine Astrovirus [ 168 ], Lactate–Dehydrogenase–Elevating–Virus (LDEV) [ 169 ], Rodentibacter sp. [ 153 , 162 ], Helicobacter sp.…”
Section: How To Ensure Qualitymentioning
confidence: 99%
“…PCR on nucleic acids extracted from filters has proven to be more sensitive and effective than the use of sentinels for the detection of specific pathogens such as Murine norovirus (MNV) (Zorn et al, 2017 ), Mouse hepatitis virus (MHV) (O’Connell et al, 2021 ), Sendai virus (Compton et al, 2004b ), Murine Astrovirus (Korner et al, 2019 ), Pasteurella pneumotropica (Miller et al, 2016 ), Helicobacter spp. (Mailhiot et al, 2020 ), Lactate dehydrogenase elevating virus (LDV) (Luchins et al, 2020b ), Pneumocystis murina (Miller and Brielmeier, 2018 ), fur mites (Hanson et al, 2021 ) ( Gerwin et al, 2017 ) ( Korner et al, 2019 ) Protozoa and pinworm (Kapoor et al, 2017 ) (Dubelko et al 2018 ) (Bauer et al, 2016 ). This rodent-free approach is ethical reducing animals and animal manipulations.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified pathogenic and other fungi and bacteria in animal facilities for rodents (Carriquiriborde et al 2020, Na et al 2010, Kunstyr et al 1997, and quality control recommendations for ensuring rodent health have been implemented. Nevertheless, these parameters do not cover the entire environment of animal facilities (Felasa 2014, Na et al 2010, Mailhiot et al 2020. Information regarding monitoring and maintenance of air and water microbial quality is currently available (Dawson & Sartory 2000, Kim et al 2018, Leclerc et al 2001, Edstrom & Curran 2003, Westall et al 2015, which is essential for formulating ways to detect and to control infections caused by pathogenic and opportunistic microorganisms in animal facilities (Schlapp et al 2018, Cincinelli & Martellini 2017, Mansfield et al 2010, Kunstyr et al 1997, Ooms et al 2008, Westall et al 2015.…”
Section: Introductionmentioning
confidence: 99%